THE IMPLEMENTATION EFFECT BLENDED LEARNING APPROACH ON ACCOUNTING KNOWLEDGE AND GENERIC SKILLS - Susilowati, Nurdian; Latifah, Lyna (Journal of Accounting and Business Education, 2016)
The objectives of the study were; (1) to investigate the influence of blended learning approach implementation towards the accounting knowledge and (2) to investigate the influence of blended learning approach implementation towards the generic skills. It was a quantitative research approach with quasi experimental research design with static group comparison design. The samples of the study were economics education students which were taking the Introduction to Accounting Subject at the materials of adjustment entries. Data were analyzed by descriptive analysis and inferential analysis (independent sample t-test). The results of the study showed that there were differences on studentsâ learning outcomes for the materials of adjustment entries between students who were taught by blended learning approach and those who were taught by conventional method. Moreover; there were also differences on generic skills between those two approaches. Studentsâ generic skills who were taught by blended learning approach were bettter than those who were taught by conventional method.Keywords: blended learning, accounting knowledge, generic skills, accounting education students